Governing Cemeteries - Van Den Breemer, Rosemarie (2021)
How do states respond to the new diversity? Providing a striking image of societal accommodation through the prism of cemeteries, this book compares state responses to Muslim and humanist burial needs. Such accommodation is typically understood in terms of national models. French laïcité, Dutch pillarization, or Norwegian establishment, authors argue, explain how these countries react to newcomers. This book shows that, upon closer scrutiny, policy responses follow distinctive logics when compared between levels of governance. Furthermore, it shows that we have to look at material solutions as well. While indeed large legal and discursive national differences between states remain, in praxis they do the same. Synthesizing a religious governance framework from the social sciences with insights from post-olonial and religious studies, the book suggests a methodologically more coherent research agenda for the comparative study of religion, secularism, society and state. "This comparative and multi-level study of state responses is confronted with huge complexity. Its most important ‘institutional (material and legal) and discursive policy outcomes’ are summarized (277ff): First the legal frameworks, the legal and discursive outcomes reveal strong national differences in line with the respective state-organized religions legacies (laicité, pillarization, establishment); second, the differences between national policies and existing provisions are less clear re. existing material provisions; third, embedded municipal practices show no national differences and no clear relevance of state-church legacies. However, discursively the study finds huge differences in how agents frame and talk about these practices.Almost all existing theoretical and methodological approaches - such as ‘secularism’ (including ‘multiple secularisms’, ‘post-secularism’) - do not take these complexities seriously into account, focusing on one concept only (wrong ‘Leitdifferenz’), neglect different meanings of terms for agents in the field and the importance of different levels, times, issues and minorities. This study highlights minimally necessary complexity without drowning in complexity. It draws clear conceptual, theoretical and methodological lessons also in a broader sense for the study of governance of religious and cultural diversity and for the governance of migrations. It is a must read." (Veit Bader Professor Emeritus, University of Amsterdam) "Van den Breemer's fascinating study of the religious governance of cemeteries by secular state institutions proves that cemeteries have become a privileged site to observe empirically the various ways in which the dual accommodation of religious-secular and multi-religious diversity takes place in today's post-secular Western European societies." (José Casanova, Professor Emeritus, Georgetown University and senior fellow at the Berkley Center for Religion, Peace and World Affairs)